Numerical modelling of pot furnace to oxidize iron ore pellets in OpenFOAM - Sivasankar, Hemanth Kumar; Sridhar, Sriram (My University, 2021)
With the rising environmental issues within the mining industry, it is vital to go fossil-free in fuel selection while working with processes such as combustion and heating. Today fossil fuels such as coal and oil are used for heating and sintering of pellets. The green balls (iron ore concentrate) are heated to produce pellets. The production of green balls are done using bentonite as a binder in the pellet feed which is subsequently rolled. In turn, these green balls are dried, heated, and oxidized before sintering to make them suitable for the metallurgical process. The study of pelletizing process is done using an experimental pot furnace. The pot furnace aids us with the measured data when the green balls are heated within the furnace with different gas compositions. Pellet bed samples are collected to support further analysis. This process is verified using an open-source platform that contains an oxidation model built with the platform. A solver suitable for this pur pose is chosen and used in accordance to fulfill the objective of creating a numerical model of this pot furnace used in experiment. Before performing the pot furnace simulations with the chosen solver, a verification study is performed between a mov ing bed of pellets and a fixed bed of pellets for a smaller domain and it is found that the chosen solver is suitable for a fixed bed case. The pot furnace simulations are performed with two different activation energies obtained from literature’s. It is concluded that the activation energy and oxygen supply plays a vital role in con version process.
Keywords: OpenFOAM, reactingHeterogenousParcelFOAM, Fossil free, Pellets, Par ticle positioning, Activation energy, Magnetite, Hematit